What’s the Impact with Congressional Aides? A Study of Communication Attitudes and Behaviors - Kristina M. Boone; Mark Tucker; Jackie M. McClaskey (Journal of Applied Communications, 2002)
This article reports findings from an evaluation study of the USDA Science and Education Impact Fact Sheet Program. The program was established in 1995 to communicate tangible effects of USDAExtension programming to help maintain investment in land-grant and USDA research and educational programs. The single-page Impact Fact Sheets, which address such topics as agriculture and the environment, parenting, and waste management, have been distributed to stakeholders through mail and personal visits and distributed to states for their own use. Impact information is also maintained on the National Impact Database. This paper reports results from both qualitative and quantitative data collection methods among congressional aides in June 2000. Results revealed that the average respondent was a 27-year old male who had served in his current position for one to three years.